Caracterización química y valoración nutritiva del rastrojo de arroz (Oryza sativa L.), en los cantones Macará y Zapotillo de la provincia de Loja. - Torres Poma, katherine del Cisne (2018)
The present investigation was oriented to carry out the chemical characterization of the stubble of rice (Oryza sativa L.), in the cantons Macará and Zapotillo of the province of Loja; It was worked in two stages, the first consisted in the collection of field samples for which a list of owners was made and three farms were selected for each variety, by random sampling in each property was obtained 1 kg of sample for the bromatological analysis and digestibility; the second stage was developed in the Laboratory of Bromatology and Fifth Experimental Punzara, belonging to the National University of Loja, where the following variables were analyzed: dry matter, ashes, crude protein and crude fiber, the in situ digestibility of the matter was carried out dry using two fused ovines, determining the kinetics of degradability in six times (0, 6, 12, 24, 48 and 96 hours), the metabolizable energy was also calculated according to the digestibility of the dry matter in the time of 48 h . An analysis of variance and Tukey test was performed for comparison between averages, using the statistical program SAS, statistical difference was found with respect to dry matter among provenances, not between varieties; regarding the percentage of protein, significant differences were found between varieties, being similar according to provenance. The highest percentage of degradability corresponds to the stubble of the Zapotillo canton with 38.7% in relation to those of the Macará canton with 35.6%. The highest percentage of degradability occurs in the period of 24 to 48 hours and subsequently the degradability is minimal. The energy content did not present a significant difference (p = 0.30) according to the provenance or the variety. Keywords: rice stubble, varieties, degradability, in situ